MACROZOOBENTHOS DIVERSITY AS A BIOINDICATOR OF WATER CONDITIONS IN TANETE RILAU SUBDISTRICT, BARRU REGENCY: A STUDY OF COMMUNITIES, SEDIMENTS, AND ENVIRONMENTAL PARAMETERS - Kamaruddin; Muh. Fahreza Suryadi; Muhammad farid Samawi; Amir Hamzah Muhiddin (Hasanuddin University, 2026)
Tanete Rilau Subdistrict in Barru Regency is a coastal area facing environmental pressures due to anthropogenic activities such as settlements, fishponds, and coastal development. This study aims to analyze the diversity of macrozoobenthos as a bioindicator of water conditions in the area. The research was conducted in March 2026 at three observation stations: the fishpond area (Station 1), mangrove ecosystem (Station 2), and settlement area (Station 3). The results found 8 species of macrozoobenthos from the phylum Mollusca (7 species of Gastropods and 1 species of Bivalvia), with a total of 61 individuals. The abundance of individuals ranged from 3–28 ind/m², with the highest abundance at Station 1 (28 ind/m²) and the lowest at Station 3 (3 ind/m²). The diversity index (H’) ranged from 0 to 1.32, categorizing the water quality as low to moderate. Station 2 showed the highest diversity (1.32), while Station 3 showed single species dominance by Clypeomorus pellucida with a dominance index (C) of 1. Sediment analysis showed dominance of fine to very fine sand fractions with total organic matter content (TOM) ranging from 5.01% to 34.88%. PCA analysis confirmed that variation in environmental conditions is controlled by the interaction of temperature, salinity, pH, DO, and TOM, which directly affect the macrozoobenthos community structure at the research sites.